2009
DOI: 10.1103/physrevb.80.064515
|View full text |Cite
|
Sign up to set email alerts
|

Existence and stability analysis of finite0π0Josephson junctions

Abstract: We investigate analytically and numerically a Josephson junction on a finite domain with two -discontinuity points characterized by a jump of in the phase difference of the junction, that is, a 0--0 Josephson junction. The system is described by a modified sine-Gordon equation. We show that there is an instability region in which semifluxons are spontaneously generated. Using a Hamiltonian energy characterization, it is shown that the existence of static semifluxons depends on the length of the junction, the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It was reported that the microwave power needed to switch the junction into a resistive state depends on the magnitude of the eigen frequency to be measured. The eigen frequency of the ground state in Josephson junctions with one and two phase-shifts has been calculated theoretically in [43][44][45][46][47][48] and confirmed experimentally in [49,50]. The experimental measurements were made by applying microwave radiation of fixed frequency and power to the Josephson junction.…”
Section: Introductionmentioning
confidence: 73%
“…It was reported that the microwave power needed to switch the junction into a resistive state depends on the magnitude of the eigen frequency to be measured. The eigen frequency of the ground state in Josephson junctions with one and two phase-shifts has been calculated theoretically in [43][44][45][46][47][48] and confirmed experimentally in [49,50]. The experimental measurements were made by applying microwave radiation of fixed frequency and power to the Josephson junction.…”
Section: Introductionmentioning
confidence: 73%
“…The eigenfrequency of the ground state in the simplest case of Josephson junctions with one and two phase-shifts has been theoretically calculated in [7,8,9,10,11,12]. More importantly, the eigenfrequency calculation in the former case has been confirmed experimentally recently in [13,14].…”
Section: Introductionmentioning
confidence: 91%